TINJAUAN YURIDIS TERHADAP PELAKSANAAN FUNGSI KEPALA BIDANG TATA RUANG DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN PELALAWAN BERDASARKAN PERATURAN BUPATI NOMOR 16 TAHUN 2016 - Riza Megia Lestari; Mexsasai Indra; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Supervision and Spatial planning that are not properly implemented in Pelalawan district in accordance with law No. 16 of 2016 regarding the position, organizational structure, duties and functions, as well as work service and spatial planning for Pelalawan Regency of course it will cause a lot of spatial planning problems that occur in Pelalawan district. Problems that arise due to poor spatial planning in Pelalawan Regency, such as; floods, air pollution, lack of supervision and monitoring of spatial use and many other problems related to lack of spatial planning supervision. So the need for the Head of Spatial Planning to supervise the existing spatial planning in Pelalawan Regency. The type of research that the author uses is sociological juridical, which is a research approach that emphasizes the legal aspects related to the subject matter to be discussed, associated with the reality that occurs in the field. In this case the authors conducted research on the Spatial Planning Sector of Pelalawan Regency and the Public Works and Spatial Planning Office of Pelalawan Regency regarding the problems of spatial planning supervision in Pelalawan Regency. From the results of this study it can be concluded that there are three main problems. First, to carry out the duties of the Head of Spatial Planning which is regulated in Regent Regulation Number 16 of 2016 concerning Position, Organizational Structure, Duties and Functions as well as Work Procedure of the Public Works and Spatial Planning Service, Ppelalawan Regency has the function of controlling and supervising the utilization of Detailed Spatial Planning (RDTR) , building and environmental plans (RTBL). The two factors that become obstacles to the Head of the Spatial Planning Division of Pelalawan Regency are Human Resources, Fund Allocation, Policy, Facility and Infrastructure Factors, and Community Legal Awareness. The third effort that the Head of the Division can make in realizing good spatial planning supervision in Pelalawan Regency is to make rules related to the use of green open space (RTH), supervise the use of spatial planning, disseminate information about spatial planning to the community, supervise control over spatial use.Key words : Supervision, Head of Division, Spatial Planning.